2014
DOI: 10.1242/jcs.144550
|View full text |Cite
|
Sign up to set email alerts
|

Non-muscle Mlck is required for β-catenin- and FoxO1-dependent downregulation of Cldn5 in IL-1β-mediated barrier dysfunction in brain endothelial cells

Abstract: Aberrant elevation in the levels of the pro-inflammatory cytokine interleukin-1b (IL-1b) contributes to neuroinflammatory diseases. Blood-brain barrier (BBB) dysfunction is a hallmark phenotype of neuroinflammation. It is known that IL-1b directly induces BBB hyperpermeability but the mechanisms remain unclear. Claudin-5 (Cldn5) is a tight junction protein found at endothelial cell-cell contacts that are crucial for maintaining brain microvascular endothelial cell (BMVEC) integrity. Transcriptional regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 56 publications
4
66
0
1
Order By: Relevance
“…At present, we cannot exclude that under inflammatory conditions the situation might be different and high levels of endothelial NF-B activity could damage the BBB, in the sense of a bell-shaped relationship between NF-B activity and BBB integrity. However, this assumption is not necessarily required, because NF-B-independent mechanisms that are instead mediated by ARNO, ARF6, -catenin, and FoxO1 increase endothelial permeability in response to inflammatory factors (Zhu et al, 2012;Beard et al, 2014). In addition, activation of NF-B in neighboring astrocytes and pericytes leads to the release of inflammatory mediators that subsequently break down the BBB (Zhang et al, 2007;Bell et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…At present, we cannot exclude that under inflammatory conditions the situation might be different and high levels of endothelial NF-B activity could damage the BBB, in the sense of a bell-shaped relationship between NF-B activity and BBB integrity. However, this assumption is not necessarily required, because NF-B-independent mechanisms that are instead mediated by ARNO, ARF6, -catenin, and FoxO1 increase endothelial permeability in response to inflammatory factors (Zhu et al, 2012;Beard et al, 2014). In addition, activation of NF-B in neighboring astrocytes and pericytes leads to the release of inflammatory mediators that subsequently break down the BBB (Zhang et al, 2007;Bell et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…These mediators trigger intracellular signaling events of the microvascular endothelium leading to changes of endothelial structure proteins which give rise to endothelial hyperpermeability. [6,7] TNFα is a cytokine released from activated leukocytes involved in mediating systemic inflammatory response syndrome (SIRS). [8] In fact, intravenous injection of TNFα induces SIRS in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that ERK phosphorylation contributes to the activation of the MLCK signaling pathway, which leads to barrier dysfunction in the vascular endothelium or intestinal epithelium [6]. Although MLCK is implicated in endothelial and epithelial barrier dysfunction [25,26], its specific role in the impairment of the esophageal epithelial barrier has not been reported. Our study provides direct evidence that ERK-mediated activation of MLCK plays a critical role in esophageal epithelial barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%